Management of Otological Foreign Bodies Impaction in Tertiary Health Care Center - Adegbiji, Waheed Atilade; Aremu, Shuaib Kayode; Aluko, AbdulAkeem A.; Olubi, Olawale (International Journal of Innovative Research in Medical Science, 2019)
Background: Otologic foreign body impaction are common ear disorder with an associated challenge due to high levels with of pre-hospital unskilled attempted removal. Aim: This study aimed at determining the prevalence, socio-demographic features, etiology, clinical presentation, management and outcome in a tertiary health care center in Nigeria. Materials and Methods: This is a prospective hospital-based study of all patients with an impacted otologic foreign body. Consented patients were studied between October 2015 and September 2017. The interviewer-assisted questionnaire was used to collect data. Analysis of obtained data was done SPSS version 16.0. Results: Prevalence of otologic foreign body impaction was 4.5%. There were 58.5% males with a male to female ratio of 1.5:1. The main type of ear foreign body impaction was 85.2% organic (living or dead) and 14.8% inorganic. Commonest otologic foreign body were a cotton bud, insects and seeds in 38.5%, 17.0% and 11.9% respectively. The foreign body was unilateral in 97.0% and bilateral in 3.0%. Left ear in 42.2% and right ear in 54.8%. The foreign body was in the external canal in 97.8% and middle ear cleft in 2.2%. Main sources of referral were self-reporting in 30.4% and general practitioners in 22.2%. Commonest predisposing factors were 31.1% allergy, 23.7% otitis externa, 15.6% earwax and 3.0% mental disorders. Conclusion: There are the different type of otology foreign body in all age group and associated predisposing factors. Pre-hospital attempt removal by unskilled sympathizers and untrained health workers leads to avoidable complications.